The Effect of Price, Location and Innovation on the Purchasing Decision of Aglonema Ornamental Plants at CV Gantina Flora Cikarang - Primaraga Sumantri Indra Wicaksana; Surya Bintarti (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to determine the influence of price, location and innovation on the purchasing decision of aglonema ornamental plants at CV Gantina Flora Cikarang. The sampling technique in this study used probability sampling technique and obtained 100 respondents. Data collection techniques include observation, dissemination of questionnaires and literature studies. The data were analyzed using SPSS program. Analytical methods to be used are validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis test. From the results of the t test states that the price partially affects positive and significant to the purchase decision, location partially affects positive and significant to purchasing decisions and innovation partially affects positive and significant towards crop purchasing decisions Ornamental Aglonema CV Gantina Flora Cikarang.